Assessing Genetic Diversity and Estimating the Inbreeding Effect on Economic Traits of Inner Mongolia White Cashmere Goats Through Pedigree Analysis - Wang, Zhiying; Zhou, Bohan; Zhang, Tao; Yan, Xiaochun; Yu, Yongsheng; Li, Jinquan; Mei, Bujun; Wang, Zhixin; Zhang, Yanjun; Wang, Ruijun; Lv, Qi; Liu, Zhihong; et al. (Frontiers in Veterinary Science, 2021)
Objective: The purpose of this study was to discover the population structure and genetic diversity of Inner Mongolia White Cashmere goats (IMCGs) and demonstrate the effect of inbreeding on live body weight (LBW), cashmere yield (CY), fiber length (FL) and fiber diameter (FD) of IMCGs. Materials and Methods: All data were collected from pedigree information and production performance records of IMCGs from 1983 to 2019. The population structure and genetic diversity were analyzed by Endog 4.8 software. Inbreeding coefficients were obtained by the pedigree package in R. Then, a linear regression model was used to analyze how inbreeding influences economic traits in IMCGs. Four levels of inbreeding coefficients were classified in this study. Variance analysis was performed to determine whether inbreeding levels had a significant effect on economic traits in IMCGs. Results: The proportions of rams and dams in IMCGs for breeding were relatively small, with values of 0.8% and 20.5%, respectively. The proportion of inbred animals in the whole population was high, with values up to 68.6%; however, the average inbreeding coefficient and relatedness coefficient were 4.50% and 8.48%, respectively. To date, the population has experienced 12 generations. The average generation interval obtained in the present study was 4.11±0.01 years. The ram-to-son pathway was lowest (3.97 years), and the ewe-to-daughter pathway was highest (4.24 years). It was discovered that LBW, CY and FL increased by 3.88 kg, 208.7 g and 1.151 cm, respectively, with every 1% increase in inbreeding coefficient, and FD decreased by 0.819 μm with every 1% increase in inbreeding coefficient. Additionally, multiple comparison analysis indicated that when the inbreeding coefficient was more than 6.25%, the LBW showed an obvious decreasing trend. The threshold value of inbreeding depression in CY is 12.5%. However, inbreeding depression has not been observed in FL and FD. Conclusion: Pedigree completeness needs to be further strengthened. The degree of inbreeding in this flock should be properly controlled when designing breeding programs.